(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
The abundance and diversity of odonate fauna were studied in four selective spots of Chittagong University Campus, Chittagong, Bangladesh from August’2016 to July’2017. A total of 928 individuals of odonates under three families was collected during the study period from the four sampling sites. Out of 25 species identified one belonged to the family Gomphidae, 13 belonged to family Libellulidae and 11 belonged to family Coenagriidae. The abundance of odonate species was highest in July’17 (13.04%) and was lowest in December’16 (4.96%). Spot 2 was a hotspot for odonates as highest number (370) was collected from this spot. A total of 196, 188 and 174 individuals were collected from Spot 4, Spot 3 and Spot 1, respectively. The members of Libellulidae (472) were dominant followed by Coenagriidae (406) and lastly Gomphidae (50). Highest species richness (SR), species diversity (H′) and species evenness (J′) values were observed in the months of May’17 (1.56±0.08), May’17 (1.29±0.08) and December’16 (0.96±0.03), respectively. But lowest such values were observed in December’16 (0.96±0.05), November’16 (0.90±0.02) and May’17 (0.81±0.05), respectively. Amongst the spots, highest SR, H′ and J′, values were observed in Spot 4 (1.40±0.10), Spot 2 (1.22±0.05) and Spot 1 (0.93±0.02), respectively, whereas, lowest such values were observed in Spot 1 (1.02±0.08), Spot 1 (1.01±0.04) and Spot 4 (0.82±0.02), respectively. Ecological conditions and seasonal fluctuation had great impact on the abundance and diversity of odonates. J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(1): 55-62